Parental and Peer Influence on the Saving Behavior of the Youth (The International Research Journal of Management Science, 2018)
This paper explores the parental and peer factors which influence the saving behavior of the youth. This paper is based on a structured questionnaire with various dimensions of the saving behavior, parental and peer influence. Judgmental and convenience sampling techniques were used to collect the data of 390 respondents from Kathmandu Valley who have completed Master’s degree and are employed. The study reveals that there is significant relationship between peer influence and saving behavior. Similarly, there is significant relationship between parental financial teaching and saving behavior. Independence, control, habit formation, encouraging saving are mechanisms that influences saving behavior. However parent’s encouragement to save highly affects the saving behavior. Therefore receiving financial teaching from parents ensures sound saving behavior.